Criteria for the evaluation of requirements management tools supporting distributed software product line engineering and management - Santillán, María Florencia (2015)
The development of software product lines (SPL) by geographically distributed teams increases the complexity of requirements management (RM) related tasks, making the support of a RM tool necessary. However, the selection of the most appropriate RM tool can be challenging, therefore the use of a comprehensive criteria list guiding the selection becomes essential. The goal of this research is to determine whether available criteria lists include comprehensive criteria for the evaluation of RM tools to be adopted in distributed SPL requirements management. This research answers the following research questions: (1) Do currently available criteria lists for RM tool evaluation allow the assessment of tools supporting distributed SPL requirements management? (2) To what extents do criteria lists support the evaluation of RM tool general features, as well as SPL requirements and distributed collaboration related features? and (3) How would a comprehensive criteria list for the evaluation of tools used in distributed SPL requirements management look like? To answer these questions a literature review and a constructive research were conducted. The review focused on fully available criteria lists for the evaluation of RM tools, as well as research in the fields of distributed collaboration and SPL to identify tool features necessary in these activities. Based on the results obtained, the constructive research was conducted to create a framework to evaluate the available criteria lists and guide the creation of the new criteria list. The analysis of the available criteria lists left in evidence the lacking of a list with comprehensive criteria for the evaluation of tools features supporting distributed SPL requirement management. Therefore, a new list was created taking as a base the criteria list found most comprehensive and extending it with new requirements. The evaluation framework, the comparison of available criteria lists and the newly created criteria list, present a contribution to current research, however, further research is required to validate these results.